Fat mass as the main contributor to the Body Mass Index of obese patients in Banyumas Regency - Candrawati, Susiana; Fatchurohmah, Wiwiek; Mustofa, Mustofa; Muflikhah, Khusnul; Wibowo, Yudhi (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4415, 2021)
Body Mass Index (BMI) measurement is the indicator most often used to identify whether a person is obese or not. However, BMI is not always synonymous with body fat mass because many other body components that play a role in determining BMI, such as muscle mass and bone mass. This study aims to determine whether the BMI of obese patients can represent body fat mass. This study was a cross-sectional study. A total of 76 obese women aged 18-34 years were taken by consecutive sampling. The examination of height and weight were performed to determine the BMI. Meanwhile, the measurements of fat mass, muscle mass, and bone mass were carried out using a bioelectric impedance analyzer (BIA). Analysis of data used Pearson correlation test and Multiple Linear Regression analysis. The level of significance was at p<0.05. The results of the Pearson correlation test showed that there was a significant correlation between fat mass, muscle mass, bone mass, and BMI (p=0.000). Multivariate test using Multiple Linear Regression analysis showed that only fat mass has a significant relationship with BMI (p=0.000), R square=0.978, and the regression equation BMI = -2.860+0.807 fat mass. The main contributor to the BMI of obese patients in Banyumas was fat mass. For every 1% increase in fat mass, the BMI will increase by 0.807